Effects of a liquid (neolac1) and dry feed combination fed in varying durations on weanling pig performance - Sulabo, R.C.; Groesbeck, C.N.; Benz, J.M.; McKilligan, D.; Goodband, Robert D.; Tokach, Michael D.; DeRouchey, Joel M.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
One hundred eighty pigs (initially 11.4 lb and 18 days of age) were used in a 28-d growth assay to determine the effects on nursery pig performance of combining a complete liquid feed (Neolac) with dry feed for various durations. Pigs were randomly allotted to experimental treatments consisting of: dry feed only (control) or Neolac provided for a period of 3 and 7 days in combination with dry feed. Overall, pigs fed the liquid-dry feed combination had a greater ADG (P<0.01) than did the dry-fed pigs until d 7 after weaning. Weight gains obtained during this period were not maintained until the end of the nursery period, regardless of the duration of liquid feeding. Both dry matter intake (DMI) and DM feed/gain increased (P<0.01) as a result of liquid feeding. Pigs provided liquid feed for 7 d also had a higher DM feed/gain (P<0.06) than that of the dry-fed controls in all periods. Feeding a liquid complete diet for various durations, in combination with dry feed, only had positive effects on growth rate immediately after weaning, but did not have lasting gains to influence overall nursery performance. Further experiments are needed to determine whether the improvement in initial feed intake with liquid feeding will reduce “starve-outs” and mortality.
Keywords: Nursery pig; Liquid feed; Growth; Swine